Optofluidic sensors based on bragg gratings - Lee, S.M.; Shin, B; Seitkan, A; Myrzagaliyeva, A; Medeubayeva, B (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
This paper describes the optical planar waveguide Bragg grating including silica waveguide, polymeric waveguide, and silicon-on-insulator (SOI) waveguide in application for biosensors. Topic includes design and fabrication of the etched planar waveguide single Bragg grating and the polymeric & SOI planar waveguide Bragg grating Fabry-Perot cavity optical refractive index sensors. It is shown that the higher the refractive index of the medium, the more the resonance peak of a sensor moves. The Bragg grating cavity is more sensitive than the single Bragg grating at the same wavelength area. Therefore, a Bragg grating with a cavity area is more sensitive than the single Bragg grating. In addition, the shorter FP cavity waveguide could reveal much more sensitivity than the longer one, which will be promising to scale down the sensors to be so nanosized that extremely low concentration of molecules can be detected. The sensor developed in this study shows much promise in the application of biomedical diagnostics such as a biosensor and/or environmental monitoring biochemical sensors.